The First-Year Student Experience - Catherine Picton; Chi Baik (Student Success)
This special issue of Student Success celebrates the work of Professor Ella Kahu and her substantial contribution to the advancement of our collective understanding of student engagement. In June 2024 Professors Karen Nelson and Chi Baik, and Dr Cat Picton sat down with Ella for a reflective conversation about her work, and additional insights in her theorising and research on student experience and engagement. In this special issue, we present the interview transcript in three parts and showcase Ella’s key publications.